2019
DOI: 10.1038/s41388-019-0962-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the TR4 nuclear receptor-mediated lncTASR/AXL signaling with tretinoin increases the sunitinib sensitivity to better suppress the RCC progression

Abstract: Renal cell carcinoma (RCC) is one of the most lethal urological tumors. Using sunitinib to improve the survival has become the first-line therapy for metastatic RCC patients. However, the occurrence of sunitinib resistance in the clinical application has curtailed its efficacy. Here we found TR4 nuclear receptor might alter the sunitinib resistance to RCC via altering the TR4/lncTASR/AXL signaling. Mechanism dissection revealed that TR4 could modulate lncTASR (ENST00000600671.1) expression via transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Therefore, drug resistance studies have always been a hot spot for oncologists. Our previous results indicated that TR4 nuclear receptor-mediated lncTASR/AXL signaling promoted RCC SUN resistance, and this effect could be reversed by tretinoin [ 28 ]. YB1 transcriptionally regulates the expression of multiple-drug resistance-associated genes to mediate multidrug resistance in a variety of tumors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, drug resistance studies have always been a hot spot for oncologists. Our previous results indicated that TR4 nuclear receptor-mediated lncTASR/AXL signaling promoted RCC SUN resistance, and this effect could be reversed by tretinoin [ 28 ]. YB1 transcriptionally regulates the expression of multiple-drug resistance-associated genes to mediate multidrug resistance in a variety of tumors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Our studies also substantiate early findings that noncoding RNAs play a crucial role in the initiation and progression of multiple cancers. [46][47][48][49][50] Compared to their linear counterparts, the circRNAs are widely and highly expressed in a variety of human cells 51 and are less prone to be degraded by RNA exo-enzymes due to their unique closed-loop structure 52 and may function by regulating the oncogenic or suppressor genes to intervene with tumor progressions. 20,53 Previous studies demonstrated that DHX9 inhibits the synthesis of circRNAs through binding to their flanking inverted complementary sequences and inhibiting the pairing of these sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small molecule, tretinoin, was also reported to suppress RCC progression and affect sunitinib sensitivity via directly inhibiting the function of TR4. 21 As fact, the potential anti-cancer role of tretinoin in TC has been recognized many decades ago. It is possible that the anti-cancer effect of tretinoin on TC relies on its inhibition on the function of TR4.…”
Section: Discussionmentioning
confidence: 99%